VISUALISASI DATA PADA APLIKASI SATU DATA KOTA JAMBI - salam, alfu; Zulfikar, Zulfikar; Afdianda, Afdianda (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
Information System is a combination of software and hardware on devices that have high mobility to make it easier for users to store, receive, process and distribute data to other users. One form of application designed by the Office of Communication and Informatics (Diskominfo Kota Jambi) in information technology-based innovation to realize Jambi Smart City based on IOS and Android is the SATU DATA application which was launched on October 3 2022. Satu Data Jambi City is an application which is used for the management of sectoral statistical data for Jambi City Government. The presence of this one data application is one of the efforts in realizing the One Data Indonesia Program. The Jambi City One Data application is expected to be able to meet data needs in planning, implementing, monitoring, and evaluating the implementation of Jambi City Government development.